Manusia Mencari Makna dalam Pergulatan Kaum Eksistensialis - Agustinus Purnama (Jurnal Orientasi Baru, 2010)
Sren Kierkegaard triggered a movement of the existentialist philosophical schools. He brought back philosophy to the real meaning of human life. The true meaning does not depend on a speculative truth, but on the real life existence. Jean Paul Sartre put emphasis on the free choice to grasp a real meaning of life. One makes choice from some alternatives. Subsequently one has to be responsible of ones choice. Sartres philosophical idea and statements became favorite of his time. Gabriel Marcel wrote his philosophical reflection with his high appreciation to the human being as mystery. The relation between I and thou, even I and Thou have given a different angle to Sartres. What are the significance of the existentialist schools for our contemporary society?